Developments in aqueous polyurethane and polyurethane-acrylic dispersion technology. Part II. Polyurethane-acrylic dispersions and modification of polyurethane and polyurethane-acrylic dispersions - Kozakiewicz, J. (Polimery, 2021)
Part I of the review that concerns the developments in aqueous polyurethane dispersions (APUD) and aqueous polyurethane-acrylic dispersions (APUAD) technology was recently published. In the present paper (constituting Part II of the review) synthesis and characterization of aqueous polyurethane-acrylic dispersions (APUAD) which have hybrid particle structure and produce films and coatings exhibiting much better properties than those produced from blends of APUD and acrylic polymer dispersions are reviewed based on recent literature data. Possibilities of crosslinking the films and coatings produced from APUD and APUAD and of obtaining filled composites, specifically nanocomposites, from those dispersions are also demonstrated, and currently reported applications of those dispersions are briefly summarized. The most important developments and areas where further research may still be required are suggested with regard to synthesis and characterization of APUAD as well as to crosslinked and filled systems involving APUD or APUAD.